Application Of Podbean Video Lesson In Social Studies Learning At Junior High School - Zalda Maulidia; , Nanda Rizqy Julian Nugraha; Wahyunengsih (Pimpinan Cabang Muhammadiyah Kramat Jati, 2025)
This study aims to explore the effectiveness of using the Podbean application as a podcast-based learning medium in Social Studies (IPS) at the junior high school level. Employing a qualitative method with a literature review approach, the research analyzes various academic sources related to the implementation of digital audio technology in education. The findings indicate that the use of Podbean significantly enhances students' understanding, learning engagement, and flexibility in accessing educational content. Podcasts are considered easy to understand, communicative, and aligned with current curricula and the needs of students. In addition to supporting cognitive learning, this medium also contributes to character education. However, aspects such as teacher reflection and the development of students' affective domains are still underexplored in the reviewed literature. Therefore, a more systematic implementation and further empirical research are needed to examine the impact of podcasts on student learning outcomes comprehensively.